Effect of caffeine intake on pain perception during high-intensity exercise - Astorino, T. A.; Terzi, M. N.; Roberson, D. W.; Burnett, T. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Caffeine has been shown to reduce leg-muscle pain during submaximal cycle ergometry, as well as in response to eccentric exercise. However, less is known about its analgesic properties during non-steadystate, high-intensity exercise. The primary aim of this study was to examine the effect of 2 doses of caffeine on leg pain and rating of perceived exertion (RPE) during repeated bouts of high-intensity exercise. Fifteen active men (age 26.4 ± 3.9 yr) completed 2 bouts of 40 repetitions of"all-out" knee extension and flexion of the dominant leg at a contraction velocity equal to 180°/s. Before each trial, subjects abstained from caffeine intake and intense exercise for 48 hr. Over 3 days separated by 48 hr, subjects ingested 1 of 3 treatments (5 mg/kg or 2 mg/kg of anhydrous caffeine or placebo) in a randomized, single-blind, counterbalanced, crossover design. Leg-muscle pain and RPE were assessed during and after exercise using established categorical scales. Across all treatments, pain perception was significantly increased (p < .05) during exercise, as well as from Bout 1 to 2, yet there was no effect (p > .05) of caffeine on pain perception or RPE. Various measures of muscle function were improved (p < .05) with a 5-mg/kg caffeine dose vs. the other treatments. In the 5-mg/kg trial, it is plausible that subjects were able to perform better with similar levels of pain perception and exertion.